Oceanographic Data of the 43rd Japanese Antarctic Research Expedition from December 2001 to March 2002 - キノシタ, ヒデキ; ノサカ, タクマ; Kinoshita, Hideki; Nosaka, Takuma (National Institute of Polar Research, 2005)
P(論文) departmental bulletin paper